Dividend Policy and Its Impact on Financial Performance and Corporate Social Responsibility: a Literature Study - Abdullah Abdullah; Muchriana Muchran (Pustaka Digital Indonesia, 2026)
This study aims to investigate the relationship between dividend policy, financial performance, and Corporate Social Responsibility (CSR) through a comprehensive literature review approach. Dividend policy remains a critical financial decision that not only reflects a firm's profitability but also signals its commitment to stakeholders, including its social and environmental responsibilities. The study employs a qualitative, descriptive method based on a systematic review of 20 peer-reviewed journal articles published between 2010 and 2024. The analysis reveals that dividend policy has a significant positive impact on financial performance indicators such as Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin. However, the interaction between dividend policy and CSR is more nuanced: firms with high CSR commitments tend to retain earnings for long-term sustainability projects, while firms with low CSR scores often use high dividend payouts as a signaling mechanism. Additionally, contextual factors such as governance quality, firm size, industry type, and regional economic conditions play moderating roles. The findings suggest the need for an integrative framework that considers both financial and non-financial dimensions in dividend policy formulation. This study contributes to the literature by bridging the gap between financial decision-making and stakeholder theory, offering practical insights for managers, investors, and policymakers.